10x-29=-18x+91

Simple and best practice solution for 10x-29=-18x+91 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-29=-18x+91 equation:


Simplifying
10x + -29 = -18x + 91

Reorder the terms:
-29 + 10x = -18x + 91

Reorder the terms:
-29 + 10x = 91 + -18x

Solving
-29 + 10x = 91 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
-29 + 10x + 18x = 91 + -18x + 18x

Combine like terms: 10x + 18x = 28x
-29 + 28x = 91 + -18x + 18x

Combine like terms: -18x + 18x = 0
-29 + 28x = 91 + 0
-29 + 28x = 91

Add '29' to each side of the equation.
-29 + 29 + 28x = 91 + 29

Combine like terms: -29 + 29 = 0
0 + 28x = 91 + 29
28x = 91 + 29

Combine like terms: 91 + 29 = 120
28x = 120

Divide each side by '28'.
x = 4.285714286

Simplifying
x = 4.285714286

See similar equations:

| v^3-vt^2-36v^2+36t^2=0 | | u^2-33u-70= | | 5x+(x+6)=37+3 | | u^2+3u-70= | | -23=26h-7+6 | | 5.9-3.6= | | 5.9-36= | | 0=10x-100 | | -4=-7p+1-2p-5+9p | | x^2-11xy+10y^2= | | 47-11x=15+5x | | 36-11= | | 1.3t+3(t+8.21)=37.5 | | x^2+11xy+10y^2= | | -7(3+2x)=84 | | 2x+(2x+3)+(2x+4)=2x+2x+(3x+1) | | 35+9104(72)= | | -28x-4=0 | | X(X+1)(X+2)(X+3)=840 | | x^2+7xy+10y^2= | | 190(56)716-= | | X*(X+1)*(X+2)*(X+3)=840 | | p^2-8p-20= | | -44x-728=-772 | | -13-(-7)-2= | | 10a+5x=3b | | 1/2(12x+6)= | | 32-(19)= | | -100=5x | | 3x-(2-7)=133 | | 12+(-11)= | | p^2-21p+20= |

Equations solver categories